Reconstruction of Sex Education in Dua Garis Biru Film - Irwan Tarmawan; R. Arby Fauzan Rabbani (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine the signs through the reconstruction of sex education in the film Dua Garis Biru. This research uses framing analysis method and qualitative approach. The analysis of sex education framing in the film Dua Garis Biru uses the Zhongdang Pan and Kosicki models and analyzes the syntactic, script, thematic and rhetorical parts of the scene in the film Dua Garis Biru so as to form a relationship. The results of the study, seen from the syntactic, script, thematic and rhetorical linkages resulted in a relationship that the Dua Garis Biru film was able to reconstruct the message of sex education. The film Two Blue Lines uses the concept of metaphor to reconstruct the message of sex education. The reconstruction of sex education in the film Dua Garis Biru is seen from the results of syntactic, script, thematic, and rhetorical analyzes that produce relations in the form of metaphorical signs regarding sex education without depicting vulgar scenes. The conclusion of this study is that the film Dua Garis Biru is able to reconstruct sex education with a metaphorical concept without presenting vulgar or adult scenes. This research will have an impact on a more open form of education that can be provided through signs that are not vulgar.